Formulation and Quality Evaluation of Extruded Product From Composite Blend of Maize, Sorghum and Ricebean - Lamichhane, Bandana; Ojha, Pravin; Paudyal, Bhupendra (Journal of Food Science and Technology Nepal, 2014)
This research work was based on formulation of cereal based extruded product utilizing the underutilized grains of Nepal i.e. sorghum (white variety) and ricebean (yellow variety). The formulation having 76% maize, 15% sorghum and 9% ricebean was found best through sensory analysis. While further variation in grit particle size ranging from 550 μm to 1190 μm, the product formulated with average particle size of 1090 μm was found to have best. The optimum grit size was selected by sensory analysis, chemical analysis and physico-chemical analysis. The expansion value for product of 1090 μm grit size was maximum 3.88±0.36, and minimum value 3.02±0.14 for smaller particle size 550 μm. The density was minimum, 80.46±12.72 kg/m3 for product of 1090 μm grit size and maximum, 175.33±11.89 kg/m3 for product of 550 μm grit size. The soluble fiber, β-glucan, WAI (water absorption index) and WSI (water soluble index) were found to be 6.52±0.61 % (db), 9.77±0.52 and 21.48±0.82 respectively for final product of grit size 1090 μm. DOI: http://dx.doi.org/10.3126/jfstn.v8i0.11748 J. Food Sci. Technol. Nepal, Vol. 8 (40-45), 2013